The amazing SpongeBobini - Banks, Steven. frey50; Martinez, Heather (New York : Simon Spotlight/Nickelodeon, 2007)
When Patrick is sick and can't go to the circus, SpongeBob brings the circus to Patrick.
"Based on the TV series SpongeBob SquarePants created by Stephen Hillenburg as seen on Nickelodeon"--P. facing t.p.
Keywords: Circus; SpongeBob SquarePants (Fictitious character); Circus; SpongeBob SquarePants (Fictitious character)